Assessing habitat exposure to eutrophication in restored wetlands: Model-supported ex-ante approach to rewetting drained mires. (1st April 2015) - Grygoruk, Mateusz; Bańkowska, Agnieszka; Jabłońska, Ewa; Janauer, Georg A.; Kubrak, Janusz; Mirosław-Świątek, Dorota; Kotowski, Wiktor
Abstract: A multi-model-based study was performed in order to unravel valuable fen meadow habitats' possible exposure to eutrophication, which is expected to occur as a result of the re-saturation of degraded peat soils. The framework was tested in a 3000-ha fen-drain system to be restored in the Middle Biebrza Basin (northeast Poland), where the datasets and related models were used to delineate prospective eutrophication hotspots and nutrient transport. A 1-d hydrodynamic model and a 3-d groundwater flow model were applied to constitute the hydrological response of the fen-drain system to the prospective construction and function of weirs and spillways, which are expected to induce the increase of groundwater levels in degraded fens. A groundwater particle-tracking postprocessor was applied to delineate flow pathways and discharge zones and to determine water residence time in modelled layers. Soil and habitat maps, a high-resolution digital elevation model and historic groundwater level observations were applied to the model performance, calibration and spatial analysis of prospective eutrophication hotspots where increased eutrophication of groundwater can be expected due to the re-saturation of degraded peat soils. The study revealed that the large-scale fen rewetting that occurred as a result of surface water bodies' damming can potentially result in groundwater-driven nutrient dispersion along with an enhanced nutrient transport from a fen to the adjacent water bodies. Spatial analyses showed that, although the rewetting-driven eutrophication of Molinia fen meadows located in the study area is not likely, one can expect increased nutrient discharges to adjacent drains, inducing the contamination of ox-bow lakes located along the rivers. We propose the presented methodology to be applied ex-ante to fen-rewetting projects in strategic environmental assessments of restoration projects in order to manage the potentially negative environmental consequences of fen and river eutrophication with special regard to nutrient hotspots that are likely to occur within the rewetted fens. Highlights: Degraded fen's response to rewetting can be assessed ex-ante restoration. Hydrological models and GIS can be used in fen eutrophication assessment. Rewetting-related eutrophication of fens occurs in hotspot zones. Scale of nutrient release and transfer allows to assess the risk of eutrophication. Methodology proposed can be used in management of rewetted fens.